Teacher and Peer Support as Predictors of Student Physical Education Learning Outcomes - Leko, Julian Jeminel (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2023)
Students need various social support to maintain emotional stability while participating in learning. Directions and forms of social support from teachers and colleagues help students be more expressive in participating in learning. This study examines the effect of social support on student learning outcomes using a quantitative method with a correlational design. Respondents were 41 grade 8 junior high school students who were determined using a purposive sampling technique. The Teacher and Classmate Support Scale were used to collecting data on social support and documentation of PJOK scores for the odd semester of 2022/2023 as data on student learning outcomes. Data were analyzed descriptively and through simple linear regression analysis. The study proved that teacher and peer support partially or simultaneously affected student learning outcomes. The determination value of peer support is greater than that of teacher support. Overall, social support contributes 18.1% to student learning outcomes. Students need teacher support in fair treatment, always willing when students ask for help, not comparing the performance of fellow students, and being friendly and kind to students with various conditions. Likewise, the presence of colleagues who care for each other, enjoy togetherness, help each other in difficulties, social acceptance, and empathize with others.